2015
DOI: 10.1177/0002716215572993
|View full text |Cite
|
Sign up to set email alerts
|

Creating the Black Ghetto

Abstract: Were black ghettos a product of white reaction to the Great Migration in the 1920s and 1930s, or did the ghettoization process have earlier roots? This presentation takes advantage of recently available data on black and white residential patterns in several major Northern cities in the period 1880-1940. Using geographic areas smaller than contemporary census tracts, it traces the growth of black populations in each city and trends in the level of isolation and segregation. In addition it analyzes the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Or was their distinctive location strongly influenced by their low average class position, so that those with higher status were found in more integrated settings? This is a question that has been studied through locational attainment analyses, where occupational standing can be tested as a predictor of the racial composition of people’s neighborhoods (Logan et al 2015a; Logan et al 2015b). We take a simpler approach here, using the occupational SEI to index class standing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Or was their distinctive location strongly influenced by their low average class position, so that those with higher status were found in more integrated settings? This is a question that has been studied through locational attainment analyses, where occupational standing can be tested as a predictor of the racial composition of people’s neighborhoods (Logan et al 2015a; Logan et al 2015b). We take a simpler approach here, using the occupational SEI to index class standing.…”
Section: Resultsmentioning
confidence: 99%
“…Two more recent studies have used full-count microdata from 1880 through 1930 to map Chicago’s black neighborhoods at the level of enumeration districts (areas smaller than today’s census tracts). Logan et al (2015b) reported that the Index of Dissimilarity between blacks and whites in Chicago had reached nearly .70 by 1880, well above the .60 threshold that analysts consider to be extreme segregation today. At the scale of street segments, it was even higher (Logan et al 2015a).…”
mentioning
confidence: 99%
“…In the US, segregation between white and non-white populations has been enacted through institutional policies in the form of federal housing programs, urban renewal legislation, and zoning restrictions, as well as discriminatory housing lending and real estate practices, racially restrictive covenants of neighborhood associations, and racial violence (Massey & Denton, 1993). All non-white populations have experienced segregation, although the black population has experienced uniquely high levels of segregation that were evident as early as the 1880s and gave rise to persistent discriminatory social structures that exist today (Logan, Zhang, Turner, & Shertzer, 2015; Massey & Denton, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Logan and colleagues' analyses demonstrate that race superseded class, occupation, migration status and other social characteristics that may have influenced housing patterns: "Blacks lived in black neighborhoods because of their race." 19 Scholars of early African American history provide substantial evidence to support these findings.…”
Section: Schooling Housing and The Nineteenth-century Color Linementioning
confidence: 92%